2017
DOI: 10.1111/ijau.12093
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and awareness of a misstatement effect in auditors' internal control severity judgments

Abstract: We define a misstatement effect as a tendency for auditors to take the non‐detection of a misstatement as evidence of the absence of a material weakness and test the hypothesis that it occurs unconsciously in their internal control severity judgments. In a between‐participants design, which is analogous to the practice setting, we find that auditors evaluate an internal control deficiency less severely when it has not led to a misstatement. However, in a within‐participants design, where the misstatement manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Fay et al (2015) investigated the effects of auditors' awareness of prior-years' testing strategies that have been applied to auditor's judgements, and their findings showed that auditors who possessed such awareness would use the prior-years' strategies as anchors, allowing them to highlight risk factors in specific areas of their clients' accounts and develop audit procedures accordingly. Furthermore, Asare et al (2017) investigated auditors' internal control severity judgements in cases where the auditors were aware or unaware of a misstatement outcome (i.e. as an outcome of the application of the evaluated internal control).…”
Section: Awareness Of the Profession's Reputation For Independencementioning
confidence: 99%
“…Fay et al (2015) investigated the effects of auditors' awareness of prior-years' testing strategies that have been applied to auditor's judgements, and their findings showed that auditors who possessed such awareness would use the prior-years' strategies as anchors, allowing them to highlight risk factors in specific areas of their clients' accounts and develop audit procedures accordingly. Furthermore, Asare et al (2017) investigated auditors' internal control severity judgements in cases where the auditors were aware or unaware of a misstatement outcome (i.e. as an outcome of the application of the evaluated internal control).…”
Section: Awareness Of the Profession's Reputation For Independencementioning
confidence: 99%